Norman McLaren Between the Frames - Dobson, Nichola (Animation: Key Films/Filmmakers, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Animator Norman McLaren is best known for his experimental films using pioneering techniques and his work as founder of the animation department of the National Film Board of Canada (NFB), but little mention is made of his Scottish heritage or his personal life. Nichola Dobson examines some of the key events and people in his life through a close examination of his key works and his personal papers, and discusses how influential they were. By using archive material to discover his personal identity and close readings of his films, Norman McLaren rediscovers one of the most important figures in animation history. Divided into thematic chapters of significant areas of influence, Dobson analyzes his formative years growing up in Scotland and his relationship with fellow Scot, John Grierson; the international travel which influenced him politically and creatively; the creative arts which played a vital part of his life; his collaborations with other artists and his complex, and rarely discussed, personal life. Each of these chapters considers his key films during those periods with a close detailed analysis and a further examination of his life through his correspondence with family and close friends. By featuring this previously un-published material, the book allows much of the consideration of the work to be in McLaren's own words and offers a deep insight into his vast output of films over nearly 50 years.